2017
DOI: 10.1080/1547691x.2017.1335810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exposure time, particle size and uptake pathway on silver nanoparticle effects on circulating immune cells in mytilus galloprovincialis

Abstract: Nanomaterials have increasingly emerged as potential pollutants to aquatic organisms. Nanomaterials are known to be taken up by hemocytes of marine invertebrates including Mytilus galloprovincialis. Indeed, assessments of hemocyte-related parameters are a valuable tool in the determination of potentials for nanoparticle (NP) toxicity. The present study assessed the effects from two size types of silver nanoparticles (AgNP: <50 nm and <100 nm) on the frequency of hemocytes subpopulations as immunomodulation bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…Since Ag-NPs presents remarkable broad-spectrum bactericidal properties and biocompatibility (i.e. as drug delivery agent), it makes Ag-NPs a really wide-range useful material (Bouallegui et al, 2017). In contrast, some studies reported the toxic effects of Ag-NPs such as neurovascular toxicity, astrocytes metabolic and biosynthesis suppression (Xu et al, 2015), voltage-gated sodium channels toxicity (Liu et al, 2009), as well as de structive effects on cortical cell survival through cytoskeletal and synaptic protein degradation, and mitochondrial degeneration in rats (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Ag-NPs presents remarkable broad-spectrum bactericidal properties and biocompatibility (i.e. as drug delivery agent), it makes Ag-NPs a really wide-range useful material (Bouallegui et al, 2017). In contrast, some studies reported the toxic effects of Ag-NPs such as neurovascular toxicity, astrocytes metabolic and biosynthesis suppression (Xu et al, 2015), voltage-gated sodium channels toxicity (Liu et al, 2009), as well as de structive effects on cortical cell survival through cytoskeletal and synaptic protein degradation, and mitochondrial degeneration in rats (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is also important to know that neurotoxicity might be influenced by some characteristics of the Ag-NPs such as size, shape, surface coatings, rates of silver ions release and interactions with specific cells and proteins (Teleanu et al, 2018). Incidentally, a study on circulating immune cells in mytilus galloprovincialis, a marine invertebrate, notifies that nanotoxicity of Ag-NPs is size-dependent and indirectly dependent to duration of exposure (Bouallegui et al, 2017). Another case about the size-dependent effects of Ag-NPs indicates that Ag-NPs (20nm) have high cytotoxic properties with respect to permeating and damaging cerebral microvascular structures, as compared with larger particles (40nm and 80nm) (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described by [ 31 ], mussels were separately exposed to AgNP (<50nm) for 12 h—with/without having also been exposed to inhibitor of endocytosis. For the inhibitor-treated groups, mussels (n = 10) were incubated at 100 μM amantadine (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research on Mytilus galloprovincialis mussel hemocytes discusses the connection between different endocytic pathways, AgNP cytotoxicity, and immunocyte counts [ 76 , 77 ]. Upon the blocking of CME by amantadine, small AgNPs (<50 nm) caused slight toxicity to hemocytes.…”
Section: Routes Of Agnp Uptake In Invertebratesmentioning
confidence: 99%